Seed bank and control of Rottboellia exaltata using clomazone alone and in combination with other herbicides - Correia, Núbia M.; Gomes, Leonardo J.P. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2014)
The objective was to study the seed bank and control of Rottboellia exaltata L.f. in sugarcane areas with low and high infestation levels using clomazone alone and in combination with other herbicides. Two experiments were conducted using commercial sugarcane production areas. In both areas, the sugarcane was mechanically harvested without burning, with straw ground cover at 10 and 9 tons ha-1 for the first (high infestation) and second (low infestation) experiments, respectively. Treatments were clomazone alone and in combination with tebuthiuron, hexazinone, imazapyr, flumioxazin, amicarbazone or isoxaflutole, besides sulfometuron methyl + diuron + hexazinone, and two controls untreated with herbicide: a weedy control and a hand-weeded control. In the second experiment, the clomazone + imazapyr treatment was replaced with a clomazone + ametryn treatment. Under the conditions of low (6.1 plants m-2) R. exaltata infestation, there was no difference among the herbicide treatments. With the increased infestation (19.4 plants m-2), the clomazone + imazapyr, clomazone + isoxaflutole, and sulfometuron + diuron + hexazinone treatments differed from the others and promoted better control, as reflected in the soil seed bank of the weed species and in the sugarcane stalk yield.
Keywords: Application of preemergence herbicides; Itchgrass; Raw sugarcane